Time‐invariant feed‐forward inhibition of Purkinje cells in the cerebellar cortex in vivo - Blot, Antonin (John Wiley and Sons Inc., 2016)

(untitled) (J Physiol)
KEY POINTS: We performed extracellular recording of pairs of interneuron–Purkinje cells in vivo. A single interneuron produces a substantial, short‐lasting, inhibition of Purkinje cells. Feed‐forward inhibition is associated with characteristic asymmetric cross‐correlograms. In vivo, Purkinje cell spikes only depend on the most recent synaptic activity. ABSTRACT: Cerebellar molecular layer interneurons are considered to control the firing rate and spike timing of Purkinje cells. However, interactions between these cell types are largely unexplored in vivo. Using tetrodes, we performed simultaneous extracellular recordings of neighbouring Purkinje cells and molecular layer interneurons, presumably basket cells, in adult rats in vivo. The high levels of afferent synaptic activity encountered in vivo yield irregular spiking and reveal discharge patterns characteristic of feed‐forward inhibition, thus suggesting an overlap of the afferent excitatory inputs between Purkinje cells and basket cells. Under conditions of intense background synaptic inputs, interneuron spikes exert a short‐lasting inhibitory effect, delaying the following Purkinje cell spike by an amount remarkably independent of the Purkinje cell firing cycle. This effect can be explained by the short memory time of the Purkinje cell potential as a result of the intense incoming synaptic activity. Finally, we found little evidence for any involvement of the interneurons that we recorded with the cerebellar high‐frequency oscillations promoting Purkinje cell synchrony. The rapid interactions between interneurons and Purkinje cells might be of particular importance in fine motor control because the inhibitory action of interneurons on Purkinje cells leads to deep cerebellar nuclear disinhibition and hence increased cerebellar output.